Systematic review and meta-analysis on the effect of obesity on recurrence after laparoscopic anti-reflux surgery. Issue 2 (April 2019) - Bashir, Yasir; Chonchubhair, Hazel Ní; Duggan, Sinead N.; Memba, Robert; Ain, Qurat ul; Murphy, Anne; McMahon, Jean; Ridgway, Paul F.; Conlon, Kevin C.
Abstract: Background & aims: Laparoscopic anti-reflux surgery (LARS) aims to provide relief from gastroesophageal reflux disease (GORD). With increase in the prevalence of obesity, there is a concurrent increase in obese patients requiring LARS. In addition to being a more technically difficult procedure, there is conflicting evidence regarding the effectiveness of LARS in obese patients. We performed a systematic review and meta-analysis to compare the outcomes of LARS in obese versus non-obese patients. Methods: Articles on the effects of obesity on LARS were identified from Ovid Medline, EMBASE and the Cochrane Library databases up to 30th of November 2016. Two independent searches were conducted. Data were extracted independently by two researchers. The primary outcome was recurrence, whilst the secondary outcome was operative time. Pooled data were statistically analysed using forest and funnel plots. Results: Twelve studies (3346 patients) met the inclusion criteria, with 923 patients in the obese group and 2423 patients in the non-obese group. Based on a random effects model, there was a risk ratio of 1.36 (95% CI 1.08–1.72, p = 0.009), if studies reporting recurrence objectively are analysed risk ratio of 1.53 (95% CI 1.01–2.32, p = 0.05) showing 53% increased risk of recurrence for obese patients. Using a random effects model, the difference in operative time was 13.94 min (95% confidence interval (CI) 9.33–18.55, p < 0.0001), showing an increased operative time for obese patients. Conclusion: A meta-analysis of 12 studies showed that there was greater recurrence of GORD symptoms and longer operative time relating to LARS in obese patients compared to non-obese patients.